The AE404 antibody recognizes a Pseudomonas aeruginosa PAO1 surface antigen by flow cytometry - Ayadi, Imen (Antibody Reports, 2021)
The recombinant antibody AE404 detects by flow cytometry P. aeruginosa PAO1 strain; AE409 and AF389 antibodies do not.